Synthesis and Cytotoxicity Evaluation of Panaxadiol Derivatives. Issue 1 (7th January 2020) - Xiao, Shengnan; Lin, Zhe; Wang, Xude; Lu, Jincai; Zhao, Yuqing
Abstract: In this study, 13 panaxadiol (PD) derivatives were synthesized via reactions with aromatic compounds and amino acids. Following this, the cytotoxicity of these compounds was evaluated against four cancer cell lines (human hepatoma cells HepG‐2, human lung cancer cells A549, human breast cancer cells MCF‐7, and human colon cancer cells HCT‐116) and one normal cell lines (human gastric epithelial cells GES‐1). The results showed that the panaxadiol derivatives 3, 12, and 13 showed significant inhibition of cellular proliferation against cancer cells compared with PD, and the panaxadiol derivative 12 had the lowest IC50 value for A549 (IC50 =18.91±1.03 μm ). For MCF‐7 cells, most compounds exhibited good inhibition of cellular proliferation, and the panaxadiol derivative 13 showed the strongest inhibitory effect (IC50 =8.62±0.23 μm ), which significantly increased the cytotoxicity of PD and was stronger than the positive control (mitomycin). For normal cells, all compounds exhibited low or no toxic effects; thus, these derivatives can be used to develop novel antiproliferative agents. Abstract :